Low-oxygen high-strength TZM alloy material and preparation method thereof

The preparation of TZM alloy materials in a high vacuum environment through powder metallurgy + SPS technology has solved the problems of uneven performance and high oxygen content of existing TZM alloy materials, and achieved low oxygen, high strength and high performance TZM alloy materials.

CN119753469AActive Publication Date: 2025-04-04HEFEI UNIV OF TECH +1

Patent Information

Application Number
CN202411869895.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-04
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing TZM alloy materials have uneven performance in high temperature and high vacuum environments, and the high oxygen content affects the strength and durability of the material.

Method used

Powder metallurgy + SPS technology is used to prepare low-oxygen and high-strength TZM alloy materials. By pressurized sintering in a high vacuum environment, the oxygen content is controlled below 50ppm to obtain an isometric crystal structure TZM alloy material.

Benefits of technology

The low oxygen, high strength, high performance and efficient and stable manufacturing of TZM alloy materials is achieved. The material has low oxygen content, uniform grains, high density and high tensile strength, and no subsequent heat treatment is required.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005195497680000071
    Figure BDA0005195497680000071
  • Figure HDA0005195497720000011
    Figure HDA0005195497720000011
  • Figure HDA0005195497720000012
    Figure HDA0005195497720000012
Patent Text Reader

Abstract

The invention provides a low-oxygen high-strength TZM alloy material and a preparation method thereof. According to the low-oxygen high-strength TZM alloy material, the crystal grains are of an isometric crystal structure, random orientation is achieved, all-directional performance is consistent, and the average crystal grain size ranges from 25 micrometers to 35 micrometers. The TZM alloy material has the advantages of being high in density, low in oxygen content, high in strength, high in heat dissipation capacity, good in thermal shock resistance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of powder metallurgy, and in particular relates to a low-oxygen and high-strength TZM alloy material and a preparation method thereof. Background Art

[0002] TZM alloy is formed by adding a certain amount of Ti, Zr, C and other elements to the Mo base to form a Mo-Ti solid solution strengthening phase, as well as dispersed titanium carbide and zirconium carbide strengthening phases, which can increase its recrystallization temperature and improve the high-temperature performance of the alloy. Therefore, due to its high melting point, high strength, stable high-temperature performance, high elastic modulus, small linear expansion coefficient, low vapor pressure and strong corrosion resistance, it is widely used in high temperature and high vacuum fields.

[0003] High temperature and high vacuum environment have extremely strict requirements on TZM alloy materials. For example, the target plate in the CT tube in the medical device field, the heating body in the high vacuum welding equipment field, the base material used in the material brazing field, etc., all require them to have high recrystallization temperature, good toughness and high temperature performance, which is closely related to the gas content and impurity content in the TZM alloy. The lower the gas content and the higher the purity, the better the performance of the TZM alloy. Therefore, it is very critical to prepare low-oxygen and high-strength TZM alloy.

[0004] At present, there are three main process routes for preparing TZM alloys: (1) Smelting method, which is to mix molybdenum, titanium, zirconium and other elements in a certain proportion and melt them, and then use casting or mechanical pressure processing to obtain TZM rods or slabs. The advantages of the obtained materials are low gas content, but coarse grains, high cost, low yield, etc.; (2) Powder metallurgy + rolling processing, which is to mix molybdenum, titanium, zirconium, carbon powder and other elements in a certain proportion, and then isostatic pressing, high-temperature sintering, rolling or rotary forging, and then annealing to obtain TZM products. Its main characteristics are large investment and obvious grain orientation of the grain structure; (3) Powder metallurgy + hot isostatic pressing technology, that is, the former part is powder metallurgy, and the TZM product is obtained by hot isostatic pressing. The equipment investment is large, the process cycle is long, and the grain size of the obtained product is large.

[0005] In recent years, SPS technology has unique advantages in preparing materials with high strength, high density and small grain size. The equipment is easy to operate, has a short production cycle, and is energy-saving and environmentally friendly. Therefore, the method of using powder metallurgy + SPS process to prepare low-oxygen and high-strength TZM alloys needs to be explored urgently.

[0006] In addition, if the oxygen content of TZM is too high, it may lead to the formation and aggregation of oxides inside the alloy, reduce the strength of the material, and affect the durability of the component. The lower the oxygen content of TZM, the better the toughness and processing performance of the alloy, and the higher the recrystallization temperature of the alloy, and the lower the oxidation rate of the alloy, and the longer the service life of the target plate or other high-temperature components prepared by it. Summary of the invention

[0007] Technical issues

[0008] In view of the shortcomings of the prior art, in order to achieve low oxygen content, high strength, high performance, high efficiency and stable manufacturing of TZM alloy materials, the present invention proposes a method for preparing a low-oxygen and high-strength TZM alloy material.

[0009] After careful research by the inventors of the present invention, it was found that the organizational structure of TZM has a significant impact on its performance. Figure 1 shows a scanning electron microscope image of the TZM organization prepared by the powder metallurgy + rolling processing method. Figure 1 (a) is a scanning electron microscope image of the organization along the rolling direction, and Figure 1 (b) is a scanning electron microscope image of the organization perpendicular to the rolling direction. It can be seen from it that the organization along the rolling direction is a long fibrous structure, and the organization perpendicular to the rolling direction is an irregular sheet. Therefore, along these two different directions, the performance is different, resulting in its overall performance being inhomogeneous in all directions.

[0010] In order to improve the performance of TZM, it is necessary to provide a TZM with a more uniform organizational structure.

[0011] Technical Solution

[0012] According to a first aspect of the present invention, there is provided a low-oxygen and high-strength TZM alloy material, whose grains are equiaxed, randomly oriented, have consistent allotropic properties, and have an average grain size of about 25 to 35 μm.

[0013] Preferably, the density of the TZM alloy material is 10 g / cm 3 above.

[0014] Preferably, the room temperature tensile strength of the TZM alloy material is above 380 MPa, more preferably above 390 MPa.

[0015] Preferably, the oxygen content of the TZM alloy material is 50 ppm or less, more preferably 40 ppm or less.

[0016] According to a second aspect of the present invention, a method for preparing a low-oxygen high-strength TZM alloy material is provided, which comprises the following steps:

[0017] S1: According to the component content requirements of the TZM alloy material, molybdenum powder, titanium hydride powder or titanium-containing powder, zirconium hydride powder or zirconium-containing powder and carbon powder are put into a V-type mixer or a drum mixer or a planetary ball mill for powder mixing, and a uniformly mixed powder raw material of the TZM alloy material is obtained through testing;

[0018] S2: Dry the mixed powder, mold it, press it to get the blank, and then put it into a high vacuum sintering furnace for high temperature sintering and evacuate it to 1*10 -2 ~1*10 -3 Pa, and a sintered green body is obtained; wherein the sintering conditions are as follows:

[0019] Heating rate of warm sintering: 10~60℃ / min; sintering temperature: 1750~2000℃; holding time: 0.5-5h; cooling method: cooling to room temperature with the furnace;

[0020] S3: Take out the sintered blank, put it into a corresponding graphite mold, put it into the SPS furnace cavity, and evacuate it for pressure sintering to obtain the TZM alloy material.

[0021] Preferably, in step S1, the titanium-containing powder is titanium hydride powder, the purity of which is above 99.5% and the particle size is 1 to 4 μm.

[0022] Preferably, in step S1, the zirconium-containing powder is: zirconium hydride powder with a purity of more than 99.5% and a particle size of 1 to 3 μm; and / or zirconium carbide powder with a purity of more than 99.5% and a particle size of 0.5 to 2 μm.

[0023] Preferably, the purity of the molybdenum powder is above 99.95% and the particle size is 6-7 μm.

[0024] Preferably, in step S1, relative to the total weight of molybdenum, titanium, zirconium and carbon elements, the weight contents of titanium, zirconium and carbon elements are 0.4% to 0.5%, 0.08% to 0.1%, 0.03% to 0.04%, more preferably 0.5%, 0.1%, 0.035%, respectively, and the remainder is Mo.

[0025] Preferably, after the powder in step S2 is loaded into the mold, a pressure of 30-80 MPa is applied to the powder. By applying pressure, a blank with a certain density can be obtained.

[0026] Preferably, the high-temperature sintering in step S2 is performed in a high-temperature vacuum furnace or a medium-frequency induction sintering furnace.

[0027] Preferably, in step S3, the pre-sintered blank is placed in a graphite mold, placed in an SPS furnace chamber, evacuated, and pressure sintered;

[0028] Among them, the sintering vacuum is less than 10Pa, and heating is started; heating rate: 20-60℃ / min; sintering temperature: 1500-1700℃; holding time: 5-60min; pressure range: 20-50MPa; cooling method: cooling to room temperature with the furnace and taking out.

[0029] Preferably, the method for preparing a low-oxygen and high-strength TZM alloy material comprises the following steps:

[0030] S4: performing mechanical processing on the TZM alloy material obtained in step S3.

[0031] Low-oxygen and high-strength TZM alloy materials of the desired shape can be obtained through mechanical processing.

[0032] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0033] 1. Compared with the prior art, the present invention uses powder metallurgy + SPS technology to manufacture low-oxygen high-strength TZM alloy materials with the advantages of short sintering time, low energy consumption, simple operation / process, high efficiency, etc., which can greatly reduce the production cycle and cost.

[0034] 2. The TZM alloy material prepared by the present invention has a low oxygen content, the second phase is dispersed and evenly distributed, the second matrix strengthening is carried out in a vacuum environment, the strengthening sintering time is short, the second phase precipitation and oxidation of the material are reduced, and high mechanical strength is obtained.

[0035] 3. The TZM alloy material manufactured by the present invention has the advantages of high density, strong heat dissipation capacity and good thermal shock resistance.

[0036] 4. Compared with the traditional forging or rolling method, the TZM alloy material manufactured by the present invention has equiaxed grain structure, random orientation, uniform properties in all directions, and does not require subsequent heat treatment process, but obtains better machining performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] FIG. 1( a ) is a scanning electron microscope image of the structure of a TZM alloy material prepared by a rolling method along the rolling process.

[0038] FIG1( b ) is a scanning electron microscope image of the structure of the TZM alloy material prepared by the rolling method along the vertical rolling method.

[0039] Figure 2 This is a scanning electron microscope image of the structure of the low-oxygen, high-strength TZM alloy material prepared according to Example 1. DETAILED DESCRIPTION

[0040] The present invention is described in detail below in conjunction with embodiments. The following embodiments are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating processes are given, but the protection scope of the present invention is not limited to the following embodiments.

[0041] The spark plasma sintering furnace used in the following examples is a 6020 series spark plasma sintering system produced by Sinter Land Co., Ltd. of Japan. The current type is a direct current pulse current, and the pulse sequence is 40:7.

[0042] Raw material sources and properties

[0043] Titanium hydride powder, Zhuzhou Runfeng New Materials Co., Ltd., purity greater than 99.5%, particle size 1-3μm.

[0044] Zirconium hydride powder, Zhuzhou Runfeng New Materials Co., Ltd., purity greater than 99.5%, particle size 1-2μm.

[0045] Molybdenum powder, Xi'an Feilian New Materials Co., Ltd., purity greater than 99.95%, particle size 6-7μm.

[0046] Density measurement method: Archimedes drainage method;

[0047] Tensile strength measurement equipment: in-situ tensile and compressive testing system;

[0048] Test method for oxygen content: pulse heating inert gas fusion-infrared absorption method.

[0049] Example 1

[0050] Prepare Φ30*15mm TZM alloy material according to the following steps:

[0051] (1) titanium hydride powder, zirconium hydride powder, carbon powder and high-purity molybdenum powder are placed in a drum mixer at a weight ratio of 0.5%, 0.1%, 0.035% and the remainder, respectively, and grinding balls are added to stir and mix them evenly;

[0052] (2) The mixed powder is taken out and placed in a vacuum drying oven for drying. Then, the powder is taken out and placed in a mold and the pressure is increased to 30 MPa to obtain a cold-pressed prefabricated blank. The pressed blank is placed in a high vacuum sintering furnace and vacuumed to 1*10 -2 Pa, sintering at a rate of 40 °C / min from room temperature, the final sintering temperature is 1950 °C, and it is kept warm for 2 h. After cooling to room temperature with the furnace, it is taken out to obtain a sintered blank.

[0053] (3) The sintered blank was placed in a graphite mold, placed in the SPS furnace chamber, evacuated to below 5 Pa, and sintered at a heating rate of 30 °C / min from room temperature. The final sintering temperature was 1700 °C, the pressure was 30 MPa, and the temperature was kept for 5 min. After cooling to room temperature in the furnace, the blank was taken out to obtain a dense TZM material.

[0054] (4) After removing the surface carbon paper and the carburized layer from the sintered blank, the blank is machined to obtain a TZM alloy material of a desired shape.

[0055] Figure 2 This is a scanning electron microscope image of the structure of the TZM alloy material prepared according to Example 1. It can be seen from the image that the grains are in an equiaxed crystal state, the grain size is small, about 30 μm, uniform and free of holes, etc., and the material has good density.

[0056] The TZM alloy material was subjected to an anatomical destructive test, and the density of the prepared TZM alloy material was 10.05 g / cm 3 ; The room temperature tensile strength along the axial direction is 395MPa, and the room temperature tensile strength perpendicular to the axial direction is 390MPa; the oxygen content of the TZM alloy material is 32ppm; the average grain size is about 30μm.

[0057] Example 2

[0058] Prepare Φ30*15mm TZM alloy material according to the following steps:

[0059] (1) Put titanium hydride powder, zirconium hydride powder, carbon powder and high-purity molybdenum powder into a drum mixer in a ratio of 0.5%, 0.1%, 0.035% and the remainder, respectively, add grinding balls, and stir and mix them evenly;

[0060] (2) The mixed powder is taken out and placed in a vacuum drying oven for drying. Then, the powder is taken out and placed in a mold and the pressure is increased to 30 MPa to obtain a cold-pressed prefabricated blank. The pressed blank is placed in a high vacuum sintering furnace and vacuumed to 1*10 -2 Pa, sintering at a rate of 30 °C / min from room temperature, the final sintering temperature is 2000 °C, and the temperature is kept for 2 h. After cooling to room temperature with the furnace, it is taken out to obtain a sintered blank.

[0061] (3) The sintered blank was placed in a graphite mold, placed in the SPS furnace chamber, evacuated to below 5 Pa, and sintered at a heating rate of 30 °C / min from room temperature. The final sintering temperature was 1700 °C, the pressure was 30 MPa, and the temperature was kept for 5 min. After cooling to room temperature in the furnace, the blank was taken out to obtain a dense TZM material.

[0062] (4) After removing the surface carbon paper and the carburized layer from the sintered blank, the blank is machined to obtain a TZM alloy material of a desired shape.

[0063] The TZM alloy material was subjected to an anatomical destructive test, and the density of the prepared TZM alloy material was 10.08 g / cm 3 ; The room temperature tensile strength along the axial direction is 398MPa, and the room temperature tensile strength perpendicular to the axial direction is 401MPa;

[0064] The oxygen content of the TZM alloy material is 22ppm and the average grain size is about 33μm.

[0065] Example 3

[0066] Prepare Φ30*15mm TZM alloy material according to the following steps:

[0067] (1) Put titanium hydride powder, zirconium hydride powder, carbon powder and high-purity molybdenum powder into a drum mixer in a ratio of 0.5%, 0.1%, 0.035% and the remainder, respectively, add grinding balls, and stir and mix them evenly;

[0068] (2) The mixed powder is taken out and placed in a vacuum drying oven for drying. Then, the powder is taken out and placed in a mold and the pressure is increased to 60 MPa to obtain a cold-pressed prefabricated blank. The pressed blank is placed in a high vacuum sintering furnace and vacuumed to 1*10 -2 Pa, sintering at a rate of 50 °C / min from room temperature to a final sintering temperature of 2000 °C, keeping it for 2 h, cooling it to room temperature with the furnace and then taking it out to obtain a sintered blank.

[0069] (3) The sintered blank is placed in a graphite mold, placed in the SPS furnace chamber, and evacuated to below 5 Pa. The temperature is increased from room temperature at a heating rate of 50 °C / min for sintering. The final sintering temperature is 1700 °C, the pressure is 50 MPa, and the temperature is kept for 5 min. After cooling to room temperature in the furnace, the blank is taken out to obtain a dense TZM material.

[0070] (4) After removing the surface carbon paper and the carburized layer from the sintered blank, the blank is machined to obtain a TZM alloy material of a desired shape.

[0071] The TZM alloy material was subjected to a dissection destructive test. The density of the prepared TZM alloy material was 10.10 g / cm 3 ; The room temperature tensile strength along the axial direction is 446MPa, and the room temperature tensile strength perpendicular to the axial direction is 450MPa; the oxygen content of the TZM alloy material is 18ppm, and the average grain size is about 32μm.

[0072] Comparative Example 1

[0073] Prepare Φ30*15mm TZM alloy material according to the following steps:

[0074] (1) Put titanium hydride powder, zirconium hydride powder, carbon powder and high-purity molybdenum powder into a drum mixer in a ratio of 0.5%, 0.1%, 0.035% and the remainder, respectively, add grinding balls, and stir and mix them evenly;

[0075] (2) The uniformly mixed powder is taken out and placed in a vacuum drying oven for drying. Then, it is taken out and loaded into a graphite mold and pressure is applied to 60 MPa to obtain a cold-pressed preform. Then, it is placed in an SPS furnace chamber and evacuated to below 5 Pa. The preform is sintered at a heating rate of 50 °C / min from room temperature. The final sintering temperature is 1700 °C, the pressure is 50 MPa, and the preform is kept warm for 5 min. After cooling to room temperature in the furnace, it is taken out to obtain a dense TZM material.

[0076] (3) After removing the surface carbon paper and the carburized layer from the sintered blank, the blank is machined to obtain a TZM alloy material of a desired shape.

[0077] The TZM alloy material was subjected to a dissection destructive test. The density of the prepared TZM alloy material was 10.08 g / cm 3 ; The room temperature tensile strength along the axial direction is 441MPa, and the room temperature tensile strength perpendicular to the axial direction is 445MPa; The oxygen content of the TZM alloy material is 500ppm.

[0078] The following lists the commercially available products and their performance parameters for comparison.

[0079] Table 1: Commercially available products and their properties

[0080]

[0081] Table 1 lists several commercial products in the prior art, wherein commercial product 1 is prepared by a rolling process, commercial product 2 is prepared by a rolling process + annealing at 1600°C, and commercial product 3 is prepared by a hot isostatic pressing process + annealing at 1550°C. Compared with the prior art processes listed in Table 1, the TZM alloy material prepared according to the present invention has a lower oxygen content, an equiaxed grain state, better isotropy, and no annealing is required, thereby simplifying the production process and improving product production efficiency and quality.

Claims

1. A low-oxygen high-strength TZM alloy material, whose grains are equiaxed crystal structure, randomly oriented, uniform in all directions, and an average grain size of 25 to 35 μm.

2. The low-oxygen high-strength TZM alloy material according to claim 1, wherein: The density of the TZM alloy material is 10 g / cm 3 above.

3. The low-oxygen high-strength TZM alloy material according to claim 1, wherein: The room temperature tensile strength of the TZM alloy material is above 380 MPa, preferably above 390 MPa.

4. The low-oxygen high-strength TZM alloy material according to claim 1, wherein: The oxygen content of the TZM alloy material is less than 50 ppm, preferably less than 40 ppm.

5. A method for preparing a low-oxygen high-strength TZM alloy material, comprising the following steps: S1: According to the component content requirements of the TZM alloy material, molybdenum powder, titanium hydride powder or titanium-containing powder, zirconium hydride powder or zirconium-containing powder and carbon powder are put into a V-type mixer or a drum mixer or a planetary ball mill for powder mixing, and a uniformly mixed powder raw material of the TZM alloy material is obtained through testing; S2: Dry the mixed powder, mold it, press it to get the blank, and then put it into a high vacuum sintering furnace for high temperature sintering and evacuate it to 1*10 -2 ~1*10 -3 Pa, and a sintered green body is obtained; wherein the sintering conditions are as follows: Heating rate of warm sintering: 10~60℃ / min; sintering temperature: 1750~2000℃; holding time: 0.5-5h; cooling method: cooling to room temperature with the furnace; S3: Take out the sintered blank, put it into a corresponding graphite mold, put it into the SPS furnace cavity, and evacuate it for pressure sintering to obtain the TZM alloy material.

6. The method for preparing a low-oxygen high-strength TZM alloy material according to claim 5, in, In step S1, the titanium-containing powder is titanium hydride powder with a purity of 99.5% or more and a particle size of 1 to 4 μm; and / or titanium carbide powder with a purity of 99.5% or more and a particle size of 0.5 to 1 μm; In step S1, the zirconium-containing powder is: zirconium hydride powder with a purity greater than 99.5% and a particle size of 1 to 3 μm; and / or zirconium carbide powder with a purity greater than 99.5% and a particle size of 0.5 to 2 μm; The purity of molybdenum powder is above 99.95% and the particle size is 6-7 μm.

7. The method for preparing a low-oxygen high-strength TZM alloy material according to claim 5 or 6, in, In step S1, relative to the total weight of molybdenum, titanium, zirconium and carbon, the weight contents of titanium, zirconium and carbon are 0.4% to 0.5%, 0.08% to 0.1%, 0.03% to 0.04% respectively, and the remainder is Mo.

8. The method for preparing a low-oxygen high-strength TZM alloy material according to any one of claims 5 to 7, in, After the powder in step S2 is loaded into the mold, a pressure of 30-80 MPa is applied to the powder; and / or The high temperature sintering in step S2 is performed in a high temperature vacuum furnace or a medium frequency induction sintering furnace.

9. The method for preparing a low-oxygen high-strength TZM alloy material according to any one of claims 5 to 8, In step S3, the pre-sintered blank is placed in a graphite mold, placed in an SPS furnace chamber, evacuated, and pressure sintered; in, When the sintering vacuum is less than 10Pa, start heating; heating rate: 20-60℃ / min; sintering temperature: 1500-1700℃; holding time: 5-60min; pressure range: 20-50MPa; cooling method: cool to room temperature and take out.

10. The method for preparing a low-oxygen high-strength TZM alloy material according to any one of claims 5 to 9, further comprising the following steps: S4: Mechanically process the TZM block obtained in step S3.

Citation Information

Patent Citations

  • Preparation method of TZM alloy

    CN116984608A

  • Preparation method of high-plasticity recrystallized molybdenum and molybdenum alloy

    CN117884617A

  • TiA1 based alloy, production process therefor, and rotor blade using same

    EP1127949A2

Cited By

  • Low-oxygen TZM powder and preparation method thereof

    CN120772525A

  • Preparation method and application of SPS for sintering and connecting TZM and graphite by using titanium hydride powder

    CN120817815A

  • A sintering method for connecting TZM and graphite by SPS using titanium hydride powder and application thereof

    CN120817815B